Soil Microbial Community Structure Evolution along Halophyte Succession in Bohai Bay Wetland - Mingyang Cong; Di Cao; Jingkuan Sun; Fuchen Shi (Journal of Chemistry)
It is urgent to recover Bohai Bay costal wetland ecosystem because of covering a large area of severe saline-alkali soil. To explore the relationship between halophyte herbaceous succession and microbial community structure, we chose four local communities which played an important role in improving soil microenvironment. We performed phospholipid fatty acid analysis, measured soil parameters, and evaluated shifts of microbial community structure. Results showed that microbial community structure changed significantly along succession and bacteria community was dominant. Total phospholipid fatty acid content increased in different successional stages but decreased with depth, with similar variations in bacterial and fungal biomass. Soil organic carbon and especially total nitrogen were positively correlated with microbial biomass. Colonization of pioneering salt-tolerant plants Suaeda glauca in saline-alkali bare land changed total soil microorganism content and composition. These results showed that belowground processes were strongly related with aboveground halophyte succession. Fungal/bacterial ratio, Gram-negative/Gram-positive bacteria ratio, total microbial biomass, and fungi and bacteria content could indicate the degree of succession stages in Bohai Bay wetland ecosystem. And also these findings demonstrated that microbial community biomass and composition evolved along with vegetation succession environmental variables.